Peningkatan Kemampuan Kreativitas melalui Membatik dengan Menggunakan Batik Jumputan Tiga Warna pada Anak Usia 5-6 Tahun - Syakira, Astri; Masganti Sit (Universitas Lancang Kuning, 2025)
This study aims to improve the creativity of children aged 5-6 years through three-color jumputan batik art activities at An-Nida Kindergarten. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of four stages: planning, action implementation, observation, and reflection. This study involved 11 children as subjects, consisting of 2 boys and 9 girls. The three-color jumputan batik activity was chosen because it can stimulate creativity, fine motor skills, and children's color exploration abilities. The results of the study showed a significant increase in children's creativity after following the action cycle. In the pre-action, the average percentage of children's creativity was 36%, categorized as Not Developing (BB). In the first cycle, it increased to 58%, categorized as Still Developing (MB), and in the second cycle, it reached 89%, categorized as Very Well Developing (BSB). This indicates that the three-color jumputan batik activity is effective in improving children's creativity. This study contributes to the development of creative learning methods for early childhood education, as well as opening up opportunities to use traditional Indonesian art in education to foster a love of culture in children.